Prevention and control actions of Covid-19 crisis at construction sites in Malaysia / Nur Afifah Aliaa Musa ... [et al.] - Musa, Nur Afifah Aliaa; Che Ahmad, Asmalia; Abdul Tharim, Asniza Hamimi; Mohamed Salleh, Rozana; Saarani, Puteri Sidrotul Nabihah (Universiti Teknologi MARA, Perak, 2022)
The Coronavirus disease 2019 (COVID-19) has been the global pandemic crisis and has become fatal disaster recently. Hence, preventive and control actions were announced by the government to be implemented as immediate response to the crisis. Construction site is one of the areas that contribute to high infection COVID-19 rate, which has impacted the construction activities. This study attempts to analyse the preventive and control actions of COVID-19 at construction sites in Malaysia. Using the non-probability sampling approach i.e., purposive sampling, a set of questionnaires was distributed to construction site personnels including professionals and workers. Due to the Movement Control Order (MCO) during COVID-19 crisis, the questionnaires were posted online at construction related groups via social media platforms such as WhatsApp, Telegram, Instagram, and Facebook. 112 questionnaires were received and analyse by descriptive statistic using mean. This study examined four (4) main actions which were action taken by employer, employees, at workplace and for travel considerations. Eventually, 35 actions were analysed as the prevention and control actions for COVID-19 at construction sites in Malaysia. The findings revealed that the overall mean value for all the four actions was more 4.00 but less than 4.50. This demonstrated the good implementation level on COVID-19 prevention and control action at construction sites in Malaysia. These findings confirmed that the previous research findings on the confusion on COVID-19 SOP implementation at construction sites has been overcome by the construction players at sites. This shows that awareness programs on prevention and control actions by the authorities have taken place at construction sites. The cooperation between employer and employees has successfully shifted the paradigm on the actions taken to avoid COVID-19 at workplace and during traveling. This study concludes that construction sites in Malaysia do adhere to the COVID-19 prevention and control actions as per the government rules and guidelines.